Serodiagnosis of ovine neosporosis in mosul city, iraq - Maab AL-Farwachi; Basima AL-Badrani; Wesam AL-Khafaji (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the serodiagnosis of Neospora caninum by indirect enzyme linked immunosorbent assay (iELISA) among ewes in Mosul city. Materials and Methods: Totally 288 sheep sera obtained from six farms were examined for antibodies against Neospora caninum by iELISA. Results: Antibodies were found in 35 ewes (12.2%) with prevalence of 7.3, 10.4 and 18.8% in the aborted ewes, pregnant ewes, and in the healthy non pregnant animals, respectively. Conclusion: This is the first evidence of Neospora caninum antibodies in sheep from Mosul city.